The legend of Zelda. Twilight princess - Himekawa, Akira; Werry, John (Translator); Stan!, 1964-; Waldinger, Evan; Himekawa, Akira; VIZ Media (2017)
Once upon a time, wizards tried to conquer the Sacred Realm of Hyrule. The Spirits of Light sealed the wizards' power within the Shadow Crystal and banished them to the Twilight Realm beyond the Mirror of Twilight. Now, an evil menace is trying to find Midna, princess of the Twilight Realm, and the fragments of the Shadow Crystal to gain the power to rule over both the Twilight Realm and the World of Light
"Original Japanese edition published by Shogakukan"--Colophon
"Based on the hit video game series"--Page 4 of cover
Reads from right to left in the traditional Japanese format
Rated T: Teen, ages 13 and up ; contains fantasy violence
Accelerated Reader AR
Translated from the Japanese
Keywords: Legend of Zelda (Game) -- Comic books, strips, etc; Heroes -- Comic books, strips, etc; Princesses -- Comic books, strips, etc; Quests (Expeditions) -- Comic books, strips, etc; Adventure and adventurers -- Comic books, strips, etc; Comic books, strips, etc. -- Japan -- Translations into English; Graphic novels -- Japan -- Translations into English; Young adult fiction; Fantasy fiction; Adventure fiction; Graphic novels; Action and adventure comics; Fantasy comics; Comics adaptations; Comics (Graphic works)